A Redox‐Active Heterobimetallic N‐Heterocyclic Carbene Based on a Bis(imino)pyrazine Ligand Scaffold. Issue 43 (28th August 2020) - Regenauer, Nicolas I.; Jänner, Sven; Wadepohl, Hubert; Roşca, Dragoş‐Adrian
Abstract: A new redox‐active N‐heterocyclic carbene (NHC) architecture is obtained using N‐methylated pyrazinediimine iron complexes as precursors. The new species exhibit strong π‐accepting/σ‐donating properties and are able to ligate two metal centres simultaneously. The redox activity was demonstrated by the reversible chemical oxidation of a heterobimetallic Fe 0 /Rh I example, which affords an isolable ligand‐based radical cation. The reversible redox process was then applied in the catalytic hydrosilylation of 4, 4′‐difluorobenzophenone, where the reaction rate could be reversibly controlled as a function of the catalyst oxidation state. The new NHC exhibits high electrophilicity and nucleophilicity, which was demonstrated in the reversible activation of alcohols and amines. The electronic structure of the resulting complexes was investigated through various spectroscopic and computational methods. Abstract : Symbiosis: A novel redox‐switchable N‐heterocyclic carbene architecture based on pyrazine‐diimine systems is presented. We demonstrate its ambiphilicity in the reversible activation of alcohols and amines. This scaffold is capable of ligating two metals simultaneously, and the resulting heterobimetallic complexes can be reversibly oxidised and reduced.